Metabolomics Technologies for the Identification and Quantification of Dietary Phenolic Compound Metabolites: An Overview - Anallely López-Yerena; Inés Domínguez-López; Anna Vallverdú-Queralt; Maria Pérez; Olga Jáuregui; Elvira Escribano-Ferrer; Rosa M. Lamuela-Raventós (MDPI AG, 2021)
In the search for natural products with properties that may protect against or slow down chronic and degenerative diseases (e.g., cancer, and cardiovascular and neurodegenerative conditions), phenolic compounds (PC) with benefits for human health have been identified. The biological effects of PC in vivo depend on their bioavailability, intestinal absorption, metabolism, and interaction with target tissues. The identification of phenolic compounds metabolites (PCM), in biological samples, after food ingestion rich in PC is a first step to understand the overall effect on human health. However, their wide range of physicochemical properties, levels of abundance, and lack of reference standards, renders its identification and quantification a challenging task for existing analytical platforms. The most frequent approaches to metabolomics analysis combine mass spectrometry and NMR, parallel technologies that provide an overview of the metabolome and high-power compound elucidation. In this scenario, the aim of this review is to summarize the pre-analytical separation processes for plasma and urine samples and the technologies applied in quantitative and qualitative analysis of PCM. Additionally, a comparison of targeted and non-targeted approaches is presented, not available in previous reviews, which may be useful for future metabolomics studies of PCM.